Association between Serum Cholesterol Level and Osteoporotic Fractures - Wang, Yanmao; Dai, Jiezhi; Zhong, Wanrun; Hu, Chengfang; Lu, Shengdi; Chai, Yimin (Frontiers in Endocrinology, 2018)
Objective: Previous epidemiological studies have found an association between serum cholesterol level and bone mineral density. However, epidemiological studies evaluating the association between serum cholesterol level and the incidence of osteoporotic fracture are scant. Therefore, the objective of this study was to investigate whether serum cholesterol levels in Chinese participants aged 55 years or older was associated with an increased risk of osteoporotic fracture. Materials and Methods: We performed a cross-sectional study, including 1791 participants (62.1% postmenopausal women and 213 fractures). Standardized self-administered questionnaires, physical examination, laboratory tests, and dual-energy X-ray absorptiometry examination were performed. Multivariate-adjusted logistic regression models were used to evaluate associations between serum cholesterol (total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL-C), and low-density lipoprotein (LDL-C)) levels and the osteoporotic fracture risk. Results: After adjusting for potential confounding factors, there were no associations between per standard deviation (SD) increase in TC and LDL level and an increased risk of osteoporotic fracture in total participants, and in men and women as individual groups. There was a significant association between per SD increase in HDL-C level and an increased risk of osteoporotic fracture in total participants (odds ratio [OR] 1.20, 95% confidence interval [CI] 1.03, 1.40, P = 0.023) and in women (OR 1.37, 95% CI 1.12, 1.68, P = 0.003), whereas no association was observed in men (OR 1.01, 95% CI 0.73, 1.40, P = 0.951). Additionally, we found a significant association between per SD increase in TG level and an increased risk of osteoporotic fracture in total participants (OR 1.20, 95% CI 1.04, 1.38, P = 0.015). In women, a nonlinear relationship was observed between per SD increase in TG level and an increased risk of osteoporotic fracture. The risk of osteoporotic fracture in women increased with TG level above 1.64 mmol/L (OR 1.93, 95% CI 1.24, 3.00, P = 0.0038). Conclusions: Among Chinese older adults, serum HDL-C level is significantly associated with a risk of osteoporotic fractures in women, and serum TG level is significantly associated with a risk of osteoporotic fractures overall and in women with TG above 1.64 mmol/L.